Effect of the CSF1R inhibitor PLX3397 on remyelination of corpus callosum in a cuprizone‐induced demyelination mouse model. Issue 6 (10th January 2019) - Tahmasebi, Fatemeh; Pasbakhsh, Parichehr; Mortezaee, Keywan; Madadi, Soheila; Barati, Shirin; Kashani, Iraj Ragerdi
Abstract: Multiple sclerosis (MS) is a chronic inflammatory disease affecting the central nervous system (CNS). Despite introducing multiple immunomodulatory approaches for MS, there are still major concerns about possible ways for improving remyelination in this disease. Microglia exert essential roles in regulation of myelination processes, and interaction between colony‐stimulating factor 1 (CSF1) with its receptor CSF1R is considered as a key regulator of microglial differentiation and survival. The aim of this study was to investigate possible roles for a CSF1R inhibitor PLX3397 in recovery of central myelination processes. Chronic demyelination was induced in mice by addition of 0.2% cuprizone to the chow for 12 weeks. Next, animals were undergoing a diet containing 290 mg/kg PLX3397 to induce microglial ablation. The PLX3397 treatment caused a significant decrease in the rate of expression for the CSF1/CSF1R axis, and a reduction in the protein expressions for the microglial marker Iba‐1 and for the oligodendrocyte marker Olig‐2. Findings from Luxol fast blue (LFB) staining and transmission electron microscopy (TEM) showed an increase in the rate of myelination for the mice receiving PLX3397. The rate of destruction in the nerve fibers and the extent of the gaps formed between layers of myelin sheaths was also reduced after the treatment with PLX3397. In addition, animals experienced an improvement in recovery of motor deficit after receiving PLX3397 (for all P  < 0.05). It could be concluded that PLX3397 could retain myelination in the MS model possibly through regulation of the myelin environment. Abstract : Multiple sclerosis (MS) is considered as a chronic inflammatory demyelinating disease of central nervous system (CNS) causing focal lesions in the white and gray matter, and is pathologically characterized by inflammation, demyelination, microgliosis, astrogliosis, and axonal injury. Microglia are the only cell type in the brain that express colony‐stimulating factor 1 receptor (CSF1R) under normal conditions, and that expression of this receptor is necessary for normal function of the cells. Induction of microglial ablation with the CSF1R inhibitor PLX3397 could provide a promising approach for improving chronic demyelination in neurodegenerative diseases, which is probably due to adjusting the milieu around the axons for retaining a remyelination process.